Report on the condition of the lines of the Western Union Telegraph Company : manuscript - Varley, Cromwell F. (Cromwell Fleetwood), 1828-1883.
Bound volume of a report by Varley describing test results on the effects of weather on Western Union Telegraph Company telegraph lines for the cities of the Northeast.
Electrical engineer.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Western Union Telegraph Company; Telegraph lines -- Northeastern States; Electrical engineers